Gender questions in informal sector of West Bengal: a case study - Ghosh, Sayati (Journal of Social Review and Development, 2023)
The study wishes to focus on the various questions of gender in the informal sectors of West Bengal. I chose Pingla Naya village of Paschim Medinipur for its eminent scroll painters. Scroll painting is a female-dominated art-form. I conduct a field study and form a questionnaire that attempts to answer the questions related to autonomy and entrepreneurship of women to find whether autonomy is encompassing. The relative autonomy index of women is satisfyingly high. Surprisingly, the women with such a high relative autonomy index have very low willingness for entrepreneurship. Though women were initially self-employed, male entrepreneurs are coming into the limelight after this informal art form got recognized as a micro scale industry in 2016.